Localization of external urethral orifice in coronary sulcus during urethroplasty in case of severe hypospadias accompanied by prostatic utricle cyst - Jun Lu (BMC, 2021)
Abstract Background To explore whether opening the external urethral orifice in the coronal sulcus can reduce the incidence of epididymitis after operating on hypospadias with prostatic utricle cyst (PUC) connecting to the vas deferens. Group A consisted of 3 patients with severe hypospadias and PUC undergoing cystostomy, hypospadias correction and urethroplasty, along with the relocation of the external orifice of the urethra to the coronal sulcus. Group B consisted of 4 patients having initial hypospadias repaired with meatus in the orthotopic position in the glans, presenting with multiple epididymitis after hypospadias surgery and unsuccessful conservative treatment. MR confirmed that all the Group B patients had PUC connecting to the vas deferens. Group B patients underwent urethral dilatation along with urethral catheterization, cutting of the original corpus cavernosum that encapsulated the urethra, and extension of the position of the external urethral orifice to the coronal sulcus. Results In group A, 3 children underwent bladder fistula removal 2 weeks after the operation. The penis developed normally without any complications. Four children in group B underwent stent removal 12 weeks after operation, and one patient was still stenosed and dilated again. All patients in group B were followed without epididymitis recurrence. Conclusions For patients with hypospadias complicating with a PUC, connecting to one side of the vas deferens, the positioning of the external urethral orifice in the coronary sulcus would be helpful to reduce the occurrence of epididymitis.